ANALISIS BATASAN KEBEBASAN BEREKSPRESI DALAM STAND UP COMEDY (STUDI PADA KOMUNITAS STAND UP INDO MADIUN) - Azhar, Azan; Widiantari, Maria Magdalena; Nurchayati, Zulin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This inquiry examines the boundaries of expressive freedom within the realm of stand-up comedy, specifically focusing on the Stand-Up Indo Madiun community. While freedom of speech represents a foundational democratic principle, its implementation in the Indonesian landscape is frequently constrained by cultural sensitivities and regulatory frameworks. Adopting a qualitative descriptive approach, this study investigates how comedians negotiate sensitive subject matter while adhering to professional codes of conduct. Data were gathered through intensive interviews with practitioners in Madiun, direct observation of live performances, and a systematic review of comedic scripts. The findings indicate that these constraints emerge from both internal and external dimensions. Internally, the community maintains a shared commitment to avoiding derogatory physical remarks and prioritizing intellectual humor over vulgarity. Externally, practitioners must align their content with the prevailing social values of the Madiun public and navigate the legal complexities associated with the Electronic Information and Transactions (ITE) Law. To mitigate risk, comedians employ strategic self-censorship, seeking a balance between artistic authenticity and societal expectations. The study reveals that although performers aim for radical honesty, they exercise significant caution regarding SARA-related themes to prevent communal disharmony. Ultimately, this research concludes that freedom of expression in the local comedy circuit is a dynamic negotiation between creative liberty and collective responsibility, offering valuable perspectives on communication ethics within Indonesia's regional creative industries.